2018
DOI: 10.1038/s41558-018-0255-1
|View full text |Cite
|
Sign up to set email alerts
|

Ecological winners and losers of extreme drought in California

Abstract: An unprecedented era of climatic volatility is altering ecosystems across our planet 1. The potential scale, pace and consequences of this global change have been modelled extensively 2 , yet little empirical research has quantified the impacts of extreme climate events on the composition of contemporary ecological communities. Here, we quantified the responses of 423 sympatric species of plants, arthropods, birds, reptiles and mammals to California's drought of 2012-2015-the driest period in the past 1,200 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
72
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(80 citation statements)
references
References 33 publications
8
72
0
Order By: Relevance
“…Harrison et al () found a decline in mean community specific leaf area with drought. Similar to our data, Prugh et al () identified Calandrinia menziesii as a drought ‘winner’, while Erodium spp., Bromus madritensis and Bromus hordeaceus remained unchanged. Likewise, Lupinus bicolor increased strongly both at our site and those monitored by LaForgia et al () and Prugh et al ().…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Harrison et al () found a decline in mean community specific leaf area with drought. Similar to our data, Prugh et al () identified Calandrinia menziesii as a drought ‘winner’, while Erodium spp., Bromus madritensis and Bromus hordeaceus remained unchanged. Likewise, Lupinus bicolor increased strongly both at our site and those monitored by LaForgia et al () and Prugh et al ().…”
Section: Discussionsupporting
confidence: 92%
“…Still, our findings are consistent with declines in both above‐ground cover and seed banks of exotic grasses in other California grasslands during the recent drought, paralleled by increases in some native forbs (Harrison, Gornish, & Copeland, ; LaForgia, Spasojevic, Cse, Latimer, & Harrison, ). Similarly, in a predominately native California grassland the recent drought corresponded with disproportionate declines of the most common species and compensatory increases in some rarer competitors (Prugh et al, ). Those findings suggest a hypothesis for the patterns we observed, as declines in the dominant Bromus diandrus at our site correlated with increases in both other exotic grasses and native forbs (Figure ).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…SPEI was then calculated as precipitation minus ETo over the June–September period using spei R function. We used the reverse of SPEI values as a DI (Prugh et al, ), such that DI = −1 × SPEI. Positive DI values indicate an increase of aridity while negative DI values indicate the opposite.…”
Section: Methodsmentioning
confidence: 99%
“…All models were fitted including plots nested with date as a random effect on the intercept to correct for the inflation of the residual degrees of freedom that would have occurred if we were using repeated measurements as true replicates. The nlme package in R was used to run these models(Pinheiro, Bates, DebRoy, Sarkar, & R Core Team, 2019;R Core Team, 2019). As a proxy for drought, we used the total amount of precipitation at the site 2 weeks before each sampling campaign to estimate the intensity and frequency of drought.…”
mentioning
confidence: 99%